The commercial success of the “K-Drama”: lessons to learn - Vargas Barraza, Juan Antonio; De La Cruz Alatorre, Jonathan Cuitláhuac; Vizcaíno, Antonio de Jesús (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2021)
The objective of this work is to detect the elements influencing the success of the South Korean cultural industry, known as “Hallyu”, focusing on Korean soap operas, or “K-Dramas”, which have experienced a considerable rise in the last 30 years. A recount of its origins, evolution and current moment was performed, using the documentary research method Three models highlight the characteristics of its success and may be used as a reference for Latin American cultural industries, once large producers of soap operas, which have decreased their presence in international markets in recent years. Some of the characteristics that are observed for the “Hallyu” to enjoy international popularity is the use of information technologies and the quality of their work, thereby reaching new regions with little cultural relationship with Korea. These successes are the product of cultural diffusion through the Korean government and the private industry, which have implemented joint strategies for their products to achieve international success, while improving the perception of Korea abroad.